Determination of the Composition of LDPE/LLDPE Blends via 13C NMR. Issue 1 (27th April 2020) - Monwar, Masud; Yu, Youlu
Abstract: Polyethylene film properties can be manipulated by blending linear low‐density polyethylene (LLDPE) with low density polyethylene (LDPE) resin. The accurate determination of LDPE content in those blends, however, is challenging. Differential scanning calorimetry analysis has been traditionally used to determine the LDPE content, but the result can have significant error due to several limitations. Due to co‐crystallization, significant error can also result using temperature rising elution fractionation technique. In principle, the LDPE content would be determined by 13 C NMR analysis if the short‐chain branch (SCB) content of the LDPE could be determined accurately. But unambiguous assignment of all peaks in the 13 C NMR spectrum of a LDPE is difficult, if possible. Consequently, the SCB content of LDPE cannot be determined accurately. Therefore, a new approach is required to analyze the LDPE/LLDPE blend composition by 13 C NMR on a routine basis. In this paper, a robust 13 C NMR method to determine the LDPE content in LDPE/LLDPE blends is presented. By identifying unique LDPE peaks in the 13 C NMR spectrum of a LDPE/LLDPE blend compared to that of LLDPE, the blend composition can be determined. The accuracy and precision of this method will also be discussed.